An Analytical Study of Types, Importance and Concerns of Highways in India: Exploring the Types, Importance, and Concerns of Highways in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Roads are an integral part of the transport system. A country’s road network should be efficient in order to maximize economic and social benefits. Highways are major roads and quicker routes which originally built to connect cities and towns. They play a significant role in achieving national development and contributing to the overall performance and social functioning of the community. Civil engineering plans, design and built highways in a country. Modern techniques have been brought into the field of highway construction. Highways in today’s era are famous for their capacity, efficiency and durability. They have unique importance in the development of a country. They are directly connected with the economic condition of a nation. The development and betterment in roads and highways brings the development of the concerned country. Highways are of different kinds and can be classified on various grounds. In India, Highway construction faces some problems and concerns. The present research paper is an attempt to study the Types, Importance and Concerns of Highways in India.